Simulating the viability of water institutions under volatile rainfall conditions – The case of the Lake Naivasha Basin. (January 2016) - Kuhn, Arnim; Britz, Wolfgang; Willy, Daniel Kyalo; van Oel, Pieter
Abstract: This study views the Lake Naivasha Basin in Kenya's Rift Valley as a hydro-economic system with slowly emerging basin-wide water management institutions. Possible institutions face two interlinked challenges. Firstly, large scale horticultural activities as a core economic activity in the basin require substantial and regular amounts of irrigation water, abstracted from the lake and its aquifer. The lake level and thus irrigation water availability reveal a falling trend over the last two decades, which calls for institutions aimed at restricting further expansion in water use. Secondly, the region is characterized by volatile weather conditions where periods of average and above average rainfall have alternated with prolonged droughts for centuries. That leads to highly volatile water inflows into the lake. The two challenges combined thus call for water management institutions that support sustainable water use in both the short and the long run. This study therefore investigates the effect of water institutions already existing or proposed by local stakeholder organizations on preserving target lake levels against a background of highly volatile water availability which negatively affects the economic viability of institutions. To take the absence of functioning basin-wide coordination mechanisms for water allocation into account, we employ the solution format of Multiple Optimization Problems with Equilibrium Constraints (MOPEC) in our integrated hydro-economic model. Stochastic scenario simulations with the model reveal that compliance to water regulations and thus the viability of water institutions in the Naivasha Basin would require very high penalties which are not likely to be accepted by users. Highlights: We develop a hydro-economic model for the Lake Naivasha Basin in Kenya. We simulate the local hydro-economic system under different water institutions. Formally, we solve a Multiple Optimization Problem with Equilibrium Constraints. We focus on the interaction between weather stochastics and water institutions. Results show that economic scarcity might undermine water institutions.